Efficient Labor Supply for Latin Families: Is the Intra-Household Bargaining Power Relevant? - Juan Carlos Campa\~na; J. Ignacio Gimenez-Nadal; José Alberto Molina (Institute of Labor Economics (IZA), 2018)
This paper analyzes the efficient labor supply of male and female workers in Latin American countries employing the collective model framework (Chiappori et al.,2002). Using data from Time Use Surveys for Mexico (2009) and Colombia (2012), we find evidence of Pareto-efficient labor supply decisions within households, as the collective rationality is not rejected in the two countries. We find that higher female wages are related to more labor market hours of female workers, and male workers show an altruistic behavior towards females with the increase of their labor income. Sex ratio are related to transfers of additional income from male to female workers in Colombia, which sheds light on the relevance of distribution factors in the internal decision process of the couple. Our results suggest that the distribution of bargaining power within the household is an important factor that should be considered when analyzing household decisions.
Keywords: D10; J22; 330; household; collective models; labour supply; Latin America countries